A novel active filter approach with the DSP control application - Perz, J. (1996 IEEE International Symposium on Industrial Electronics, 1996)
A novel approach to the active filtering possibilities based on the powerful DSP tools available today is presented in this paper. The active filter for the enhancement of voltage source inverter output current (VSI) has been chosen as the main subject of this research. The active filter consists of an auxiliary voltage inverter connected in parallel to the main inverter loading. In comparison to the main inverter, the filter inverter has a higher key switching frequency. This fast switching capability permits the filter inverter to reduce the main inverter current harmonic disturbances by generating additional current to the load. This current has the same value and is opposite to the existing error. The exact values of the current error and reference current are crucial for active filter performance. These data can be obtained by measurements and directly from the main inverter controller. A new classification of the active filter based on data flow between the filter controller and the controlled object has been proposed. Four types of different data management methods for filtering purposes are presented and discussed. A method useful in designing complex programmable controllers in a DSP hardware and software workshop is described. A laboratory stand for filter tests and some practical results are also presented.